Draft Second Five Year Plan of Madhya Pradesh (1956-57 to 1960-61) in Two Volumes Vol.-I - Planning Commission (Planning Commission, 1956)
The first five-year plan which has shortly closed was essentially intended to initiate a process of economic development and to lay the foundations of a more progressive and diversified economy. As a result of various development programmes and projects implemented in the first plan the economy has been strengthened and a firm foundation has been laid for a balanced and all-round economic development. It is on the gains secured in the first plan that the process of development has to be carried further in the second plan.
Government of Madhya Pradesh, Planning and Development Department